2016
DOI: 10.1002/14651858.cd008493.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative statin therapy for patients undergoing cardiac surgery

Abstract: Preoperative statin therapy for patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 131 publications
0
2
0
1
Order By: Relevance
“…For example, only same of the trials were designed with a prespecified postoperative AF as an outcome (16,29,30), and only one trial (29) included an intention-to-treat analysis of the effect on AF as detected in a systematic and blinded manner. Furthermore, a recent systematic Cochrane review of those trials showed evidence of selective reporting and publication bias (31). The suggestion that perioperative statin therapy might be associated with less severe myocardial damage derives from one randomized, placebocontrolled trial involving 200 patients undergoing CABG surgery (32) and from a non-blinded randomized trial involving 151 patients undergoing non-coronary cardiac surgery, which also reported improved left ventricular function (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, only same of the trials were designed with a prespecified postoperative AF as an outcome (16,29,30), and only one trial (29) included an intention-to-treat analysis of the effect on AF as detected in a systematic and blinded manner. Furthermore, a recent systematic Cochrane review of those trials showed evidence of selective reporting and publication bias (31). The suggestion that perioperative statin therapy might be associated with less severe myocardial damage derives from one randomized, placebocontrolled trial involving 200 patients undergoing CABG surgery (32) and from a non-blinded randomized trial involving 151 patients undergoing non-coronary cardiac surgery, which also reported improved left ventricular function (17).…”
Section: Discussionmentioning
confidence: 99%
“…Точно так же Kuhn и соавт. выявили 17 рандомизированных контролируемых испытаний, включающих в общей сложности 2138 участников [20]. Они обнаружили, что предоперационная терапия статинами снижает вероятность послеоперационной фибрилляции предсердий и сокращает пребывание пациента в отделении интенсивной терапии (ОИТ), а также в больнице.…”
Section: статины и операции на сердцеunclassified
“…Statin have been expected to reduce the development of AKI or atrial fibrillation following cardiac surgery based on its antioxidant and anti-inflammatory effects. The results from several randomized trial demonstrated that perioperative statin treatment in patients with undergo cardiac surgery reduced the development of postoperative atrial fibrillation with decreasing the concentration of inflammatory cytokines (7,8). Several observational cohort studies focusing on statin treatment as a preventive effect of AKI have been reported with conflicting results (3,4).…”
mentioning
confidence: 99%